Intermittent BRAF inhibition in advanced BRAF mutated melanoma results of a phase II randomized trial - Maria Gonzalez-Cao (Nature Portfolio, 2021)
Whether intermittent strategies of delivering drugs can improve cancer patients survival is still unclear. Here, the authors reports the results of a randomized phase II clinical trial aimed to compare the efficacy and safety of two dosing regimens (continuous and intermittent) of vemurafenib and cobimetinib combination as first-line treatment of patients with unresectable or metastatic advanced melanoma with BRAFV600 mutation